OPTIMASI PENGARUH JUMLAH SIKAT PADA MESIN PENCUCI KACANG TANAH TERHADAP KEBERSIHAN VISUAL KULIT KACANG TANAH - Tri Gesti Maharadhika; Yopi Handoyo (Universitas Islam 45 Bekasi, Fakultas Teknik, Jurusan Teknik Mesin, 2018)
Peanut washers are useful for cleaning soil that sticks and can speed up the washing process inpeanut production. Peanut washers on the market have a fairly expensive price for small andmedium businesses so that it becomes a hindrance to have a peanut washing machine for smallentrepreneurs because it requires peanut washers at a cheap price by modifying used clotheswashing machines. In the modification of peanut skin washers to determine the optimalcleanliness of the use of the optimal number of brush variations from the results of washingpeanuts, use a GUI with image processing techniques looking for normalization of RGB valuesin Matlab Software. From image processing using RGB normalization value on matlab with freevariables using variations in the number of brushes 1, 2, and 3 pcs and 1 kg peanut-fixedvariables and 40 liters of water for 10 minutes to get the optimal use of 1 brush in experiment 2using 1 brush of 60% or 6 clean beans of 10 samples rather than 2 brushes and 3 brushesbecause on 2 and 3 brushes many nuts are stuck by the handle of the brush resulting from thevolume of water parallel to the brush angle so that it is not brushed.